On certain infinite series and definite integrals - Bassali, W. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The object of this paper is to obtain the sums of certain infinite series and evaluate certain new definite integrals with simple functions. Two combinatorial identities are obtained.